2018
DOI: 10.1111/1751-2980.12652
|View full text |Cite
|
Sign up to set email alerts
|

Creeping fat in patients with ileo‐colonic Crohn's disease correlates with disease activity and severity of inflammation: A preliminary study using energy spectral computed tomography

Abstract: The quantitative analysis of creeping fat using energy spectral CT is an effective method in inflammatory evaluation in patients with CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…CT body composition parameters have been used to reflect disease activity in CD patients and predict their prognosis. Feng et al found that the λ HU of creeping fat (CF) in CD patients increased with the severity of intestinal inflammation, and the λ HU of CF around the intestinal segments without lesions was significantly higher than that in the controls [ 20 ]. Zhou et al showed an increased risk of poor prognosis in CD patients with high SAT and VAT density [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…CT body composition parameters have been used to reflect disease activity in CD patients and predict their prognosis. Feng et al found that the λ HU of creeping fat (CF) in CD patients increased with the severity of intestinal inflammation, and the λ HU of CF around the intestinal segments without lesions was significantly higher than that in the controls [ 20 ]. Zhou et al showed an increased risk of poor prognosis in CD patients with high SAT and VAT density [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Altered MAT near the affected intestinal area is considered to be characteristic of severe CD [6,[27][28][29][30]. Persistent alterations in this tissue even after endoscopic remission can be observed by magnetic resonance imaging [31], and may be associated with a complicated disease course and abdominal surgery in CD [32].…”
Section: Discussionmentioning
confidence: 99%
“…Also referred to as “creeping fat”, this layer of tissue has been thought of as a physical barrier to inflammation & inflammatory markers, controlling host immune response to translocation of gut bacteria, and immunomodulation 18 , 19 . It is now, however, evident that mesenteric fat is implicated in both pathogenesis and treatment outcomes in CD 17 , 20 especially disease activity and severity of symptoms 21 , bowel damage and stricture formation 20 , 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%